ISLAMIC FINANCIAL SERVICES AND INCLUSIVE GROWTH: EVIDENCE FROM SOME SELECTED ECONOMIES - Ayinde , Taofeek Olusola (International Journal of Islamic Banking and Finance Research, 2025)
The major attraction of Islamic finance is its equitable and fair allocation and distribution of economic resources emanating from business and social engagements. However, a growing body of literature, keeping pace with its increasing attraction, suggests that Islamic finance is unfair due to its profit-sharing tenet, which typically seeks to re-allocate profits of productive borrowers to passive lenders, despite the corresponding risk and loss sharing. This has been described not only as a disincentive to the former but also as crowds out investment and debilitates growth. Consequently, this study investigates Islamic financial services and inclusive growth in seven (7) developing Islamic countries that comprise Nigeria, Pakistan, Saudi Arabia, Malaysia, Indonesia, Qatar, and Bangladesh for the period 2015 – 2023. Using bank-specific and economic aggregate time-series annual data, the analysis technique employed is Panel Least Squares, with Panel Quantile Regression used for robustness. The results show that the property contract (i.e., Istisna) and leasing (i.e., Ijarah) are the two Islamic financial services with consistent significant impacts on inclusive growth in those developing Islamic countries. Also, the effects of both primary and secondary capital adequacy measures on inclusive growth in those economies are asymmetric and disproportionate. Notably, interest-free financial services (i.e., Qardh), which are rendered on empathetic and compassionate grounds, have had a negligible effect on inclusive growth. The findings of this study suggest that policymakers should legislate to protect the rights to private property, promoting Istisna and Ijarah, while also addressing inherent regulatory concerns. JEL Classification Codes: C33, F65, G30, O47.